The G115S mutation associated with maturity-onset diabetes of the young impairs hepatocyte nuclear factor 4α activities and introduces a PKA phosphorylation site in its DNA-binding domain - Oxombre, Bénédicte (Portland Press Ltd., 2004)
HNF4α (hepatocyte nuclear factor 4α) belongs to a complex transcription factor network that is crucial for the function of hepatocytes and pancreatic β-cells. In these cells, it activates the expression of a very large number of genes, including genes involved in the transport and metabolism of glucose and lipids. Mutations in the HNF4α gene correlate with MODY1 (maturity-onset diabetes of the young 1), a form of type II diabetes characterized by an impaired glucose-induced insulin secretion. The MODY1 G115S (Gly(115)→Ser) HNF4α mutation is located in the DNA-binding domain of this nuclear receptor. We show here that the G115S mutation failed to affect HNF4α-mediated transcription on apolipoprotein promoters in HepG2 cells. Conversely, in pancreatic β-cell lines, this mutation resulted in strong impairments of HNF4α transcriptional activity on the promoters of LPK (liver pyruvate kinase) and HNF1α, with this transcription factor playing a key role in endocrine pancreas. We show as well that the G115S mutation creates a PKA (protein kinase A) phosphorylation site, and that PKA-mediated phosphorylation results in a decreased transcriptional activity of the mutant. Moreover, the G115E (Gly(115)→Glu) mutation mimicking phosphorylation reduced HNF4α DNA-binding and transcriptional activities. Our results may account for the 100% penetrance of diabetes in human carriers of this mutation. In addition, they suggest that introduction of a phosphorylation site in the DNA-binding domain may represent a new mechanism by which a MODY1 mutation leads to loss of HNF4α function.